2016
DOI: 10.1016/j.jpainsymman.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization Scale in Spanish-Speaking Palliative Care Patients

Abstract: The Spanish adaptation of the DS has shown appropriate psychometric properties. It has been useful to differentiate between depression and the demoralization syndrome, pointing to helplessness and dysphoria as unique characteristics of demoralized palliative care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
2
32
1
1
Order By: Relevance
“…Previous studies conducted in Australia, the United States, Taiwan, Germany, Spain, and Portugal showed that age, single status, unemployment, partnership [1,20,26], gender, physical problems, social support, dignity [27,28], education, anxiety and depression [18,19,29] had significant correlations with demoralization in cancer patients. Our findings were partially consistent with the above-mentioned studies in that family support, monthly income, and education were significant factors of demoralization in cancer patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies conducted in Australia, the United States, Taiwan, Germany, Spain, and Portugal showed that age, single status, unemployment, partnership [1,20,26], gender, physical problems, social support, dignity [27,28], education, anxiety and depression [18,19,29] had significant correlations with demoralization in cancer patients. Our findings were partially consistent with the above-mentioned studies in that family support, monthly income, and education were significant factors of demoralization in cancer patients.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, some previous studies examined demoralization among refugee and migrant populations [16,17]. In recent years, the focus has shifted to cancer patients [18,19]. Based on the above literature, we would like to know how demoralization influences cancer patients in Taiwan and then make the study results available to other countries with similar situations.…”
Section: Introductionmentioning
confidence: 99%
“…28 It was originally validated among 100 patients with advanced cancer, and it consists of 5 subscales corresponding to the core dimensions of demoralization as proposed by Clarke and Kissane, 15 specifically: loss of meaning, dysphoria, disheartenment, helplessness, and sense of failure. In the oncology setting, the DS has been translated and validated in several countries, including Germany, 29 Ireland, 30 Spain, 31 and Taiwan. 32 The study by Robinson et al presented in this issue of Cancer offer the possibility to use for clinical and research purposes a shorter version of the original DS.…”
Section: Editorial/grassi and Nannimentioning
confidence: 99%
“…On this background, the Demoralization Scale (DS) has been developed, originally validated among 100 advanced cancer patients, and shown to capture the core dimensions of demoralization as proposed by Clarke and Kissane, namely, loss of meaning, dysphoria, disheartenment, helplessness, and sense of failure. Within oncology and palliative care settings, the DS has been translated and applied in several countries, such as Germany, Ireland, Taiwan, Italy, and Spain, with data confirming its construct and convergent validity with respect to other psychometric instruments, although the factor structure of the DS was different with respect to the original …”
Section: Introductionmentioning
confidence: 95%